ANALISIS PENGARUH JUMLAH KREDIT YANG DISALURKAN DAN NON PERFORMING LOAN (NPL) TERHADAP LABA PADA PT. BANK TABUNGAN PENSIUNAN NASIONAL (PERSERO),TbK KANTOR CABANG MEDAN PUTRI HIJAU - Shita Tiara (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This study aims to determine the effect of the amount of outstanding loans to profits, the influence of non-performing loans (NPLs) to the income and the effect of the amount of outstanding loans and non-performing loans (NPL) simultaneously to profit at PT. National Savings Bank (Persero), Tbk Branch Office Medan Putri Hijau. The variables in this study consisted of loans disbursed and NPL as the independent variable and income as the dependent variable.The method used in this research is descriptive method of analysis is simple and multiple linear regression, hypothesis testing, and test t and f the coefficient of determination. The test is performed by using statistical software SPSS 16.0 for Windows.Persial test results showed that outstanding loans terjadap affect earnings with a significant value of 0.5% while the NPL does not affect the profit, which amounted to 68.2% significance value. While simultaneously outstanding loans and NPLs have an influence on the profit which the value of f at 7.15 while the value and significance of the coefficient of determination 0.014 78.6%.